Socio-Economic Conditions of Home-Based Women Workers of Meerut: A Case Study - Ruby; Kumar, Dinesh (Journal of Commerce and Trade, 2022)
One-third of women in India’s non-agriculture employment sector are engaged in all kinds of remunerative work from home as a home-based worker. Some of them are working as self-employed workers and some are sub-contractor for an individual employer and intermediator. This paper tries to understand the socio-economic conditions of home-based women workers in unorganized sector engaged in various economic activities like stitching clothes and soccer ball, embroidery on saree and suit and also sticking nag on clothes with 30 sample sizes by using convenient sampling. The area of the study is Kashiram Awas Colony, lohiya nagar Meerut, Disrict of Meerut in Uttarpardesh State. The conclusion of this study is that, In order to build strength, unity and resilience government should have to need to invest in more and more co-operative societies to empower these home-based women workers. Classification-JEL: H1, J01